In Vitro Inhibition Effect of Coconut Husk Ethanol Extract towards the Growth of Escherichia coli and Staphylococcus aureus from Surgical Site Infection - Alifiana Jatiningrum; Maryani .; Amelya Augusthina Ayusari (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Surgical site infection was defined clinically, namely the existence of purulent discharge around the wound or wound cellulitis in operation. Coconut husk are known to has tannin and flavonoid as antibacterial properties. This study aimed to determine In Vitro effect of coconut husk (Cocos nucifera L.) ethanol extract towards the growth of Escherichia coli and Staphylococcus aureus from surgical site infection. Methods: This research is an experimental laboratory (post test only control group design) with a non-probability sampling technique namely consecutive sampling. Research conducted at the Microbiology Laboratory FK UNS and sampling conducted in the Microbiology Laboratory Dr. Moewardi Hospital. The independent variables are the coconut husk ethanol extract at a concentration of 1%, 20%, 40%, 60%, and 80%. Subjects were Escherichia coli and Staphylococcus aureus of surgical site infection standardized with Mc Farland 0.5. Test sensitivity on Muller-Hinton medium diffusion method with antibiotics cefoperazone/sulbactam and vancomycin as a positive control and DMSO 2% as negative control. Research results are tested with the Kruskal-Wallis test followed by Mann-Whitney test. Results: Coconut husk ethanol extract cant inhibit the growth of Escherichia coli but can inhibit the growth of Staphylococcus aureus. Based on the results of the Kruskal-Wallis test that at least there is a significant difference in inhibition between the two treatment groups (p <0.005). The results of the Mann-Whitney test showed that there were significant differences in inhibition (p <0.05) in all treatment groups, except in the group with the inhibition of the extract concentration of 40% with 60% extract concentration did not reveal any significant differences in inhibition (p > 0.05). Conclusion: Coconut husk ethanol extract cant inhibit the growth of Escherichia coli but can inhibit the growth of Staphylococcus aureus from surgical site infection by In Vitro. Keywords: Surgical site infection, Escherichia coli, Staphylococcus aureus, coconut husk